FACILITIES AND INFRASTRUCTURE AS SUPPORTING FACTORS FOR LEARNING QUALITY - irwandi, hendra; Zulhimma (STAI Ma'had Aly Al-Hikam Malang, 2025)
The rapid transformation of education in the 21st century, characterized by globalization, digitalization, and complex sociocultural shifts, demands a paradigm shift in Islamic educational institutions. This study explores the implementation of Personalized Education in an Islamic boarding school (Islamic boarding school) context through a reflective field study conducted at Darul Mursyid Modern Integrated Islamic Boarding School in South Tapanuli, Indonesia. The research focuses on the Project Roadmap of Santri Aspirations, a structured mentoring program designed to guide students (santri) in discovering their potential, setting personal goals, and aligning their aspirations with Islamic moral and spiritual values. Using a qualitative reflective methodology that combines field observation, participatory workshops, and community engagement, the study investigates how educators, mentors, and parents collaborate to integrate academic, spiritual, and personal development. Findings reveal that the Roadmap Project promotes self-awareness, motivation, and goal orientation among students, transforming teachers into reflective mentors and fostering strong partnerships between the pesantren and families. The program demonstrates the adaptability of Islamic education to modern pedagogical approaches without compromising its spiritual essence. This article argues that personalized, reflective, and value-based education can serve as a model for Islamic boarding schools seeking to balance tradition with innovation in the era of global educational reform. Keywords: Personalized Education, Islamic Boarding School, Reflective Learning, Humanistic Education, Educational Transformation, Character Formation Abstrac Transformasi pendidikan yang pesat di abad ke-21, yang ditandai dengan globalisasi, digitalisasi, dan pergeseran sosio-kultural yang kompleks, menuntut pergeseran paradigma di lembaga pendidikan Islam. Studi ini mengeksplorasi implementasi Pendidikan Personalisasi dalam konteks pesantren (pesantren) melalui studi lapangan reflektif yang dilakukan di Darul Mursyid Modern Integrated Islamic Boarding Madinah di Tapanuli Selatan, Indonesia. Penelitian ini berfokus pada Proyek Peta Jalan Aspirasi Santri, sebuah program pendampingan terstruktur yang dirancang untuk membimbing santri dalam menemukan potensi mereka, menetapkan tujuan pribadi, dan menyelaraskan aspirasi mereka dengan nilai-nilai moral dan spiritual Islam. Dengan menggunakan metodologi reflektif kualitatif yang menggabungkan observasi lapangan, lokakarya partisipatif, dan keterlibatan masyarakat, studi ini menyelidiki bagaimana pendidik, mentor, dan orang tua berkolaborasi untuk mengintegrasikan perkembangan akademik, spiritual, dan pribadi. Temuan menunjukkan bahwa Proyek Peta Jalan mendorong kesadaran diri, motivasi, dan orientasi tujuan di antara siswa, mengubah guru menjadi mentor reflektif dan membina kemitraan yang kuat antara pesantren dan keluarga. Program ini menunjukkan kemampuan pendidikan Islam untuk beradaptasi dengan pendekatan pedagogis modern tanpa mengorbankan esensi spiritualnya. Artikel ini berpendapat bahwa pendidikan yang personal, reflektif, dan berbasis nilai dapat berfungsi sebagai model bagi sekolah berasrama Islam yang berupaya menyeimbangkan tradisi dengan inovasi di era reformasi pendidikan global. Kata kunci: Pendidikan Personal, Sekolah Berasrama Islam, Pembelajaran Reflektif, Pendidikan Humanistik, Transformasi Pendidikan, Pembentukan Karakter